Folk medicinal uses of Verbenaceae family plants in Bangladesh - Rahmatullah, Mohammed (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Folk medicinal practitioners form the first tier of primary health-care providers to most of the rural population of Bangladesh. They are known locally as Kavirajes and rely almost solely on oral or topical administration of whole plants or plant parts for treatment of various ailments. Also about 2% of the total population of Bangladesh are scattered among more than twenty tribes residing within the country’s borders. The various tribes have their own tribal practitioners, who use medicinal plants for treatment of diseases. The objective of the present survey was to conduct an ethnomedicinal survey among the Kavirajes and tribal practitioners to determine which species of plants belonging to the Verbenaceae family are used by the practitioners. The Verbenaceae family plants are well known for constituents having important bio-active properties. The present survey indicated that 13 species belonging to 8 genera are used by the folk and tribal medicinal practitioners of Bangladesh. A comparison of their folk medicinal uses along with published reports in the scientific literature suggests that the Verbenaceae family plants used in Bangladesh can potentially be important sources of lead compounds or novel drugs for treatment of difficult to cure debilitating diseases like malaria and rheumatoid arthritis.